EFEKTIVITAS RELAKSASI OTOT PROGRESIF TERHADAP KADAR GULA DARAH: PENELITIAN KUASI EKSPERIMEN PADA PENDERTIA DIABETES MILITUS TIPE 2 USIA PRODUKTIF: THE EFFECTIVENESS OF PROGRESSIVE MUSCLE RELAXATION ON BLOOD SUGAR LEVELS: A quasi-experimental study in patients with diabetes mellitus type 2 of productive age - Rini Meilani; Fauzan Alfikrie; Aryanto Purnomo (Akademi Keperawatan Yarsi Samarinda, 2020)
Many Type 2 Diabetes Mellitus patients are unable to maintain normal blood sugar levels. This is caused by lack of physical activity, disobedience to treatment and obesity. The purpose of this study was to identify the effect of progressive muscle relaxation therapy on blood sugar levels of type 2 diabetes mellitus patients. The method of this study used a pretest – posttest design nonequivalent control design with statistical analysis of an indentent sample t-test. The results of the majority of the age of 45-59 years (41.7%), female sex (75%), duration of diagnosis of diabetes mellitus more than 5 years (66.7%), Obesity (41.7%) and some work as civil servants (37.5%). The difference in average blood sugar values ​​in the group after progressive muscle relaxation exercises (45.5 mg / dl) p value 0,000 (α 0.05), the difference between the progressive muscle relaxation exercise group and the control group showed the difference (44.9 mg / dl) p value 0,000 (α 0.05). Pregressive muscle relaxation is a practical therapy that can be carried out by everyone who is beneficial in reducing blood sugar levels